PENGARUH PARTISIPASI MASYARAKAT DAN KEPEMIMPINAN KEPALA DESA TERHADAP KEBERHASILAN PROYEK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT DI DESA SUKOHARJO III KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU - Eka Ubaya Taruna Rauf (e-JKPP, 2019)
This study aims to determine the effect of community participation on the success of the project, the influence of leadership on community participation, and the influence of community participation and leadership of the village head towards the success of the PNPM Mandiri Rural Project in Sukoharjo Village III Sukoharjo Sub-district, Pringsewu District. Data are needed and collected with questionnaires distributed to 180 community beneficiaries of PNPM Mandiri Perdesaan program which is divided into three strata, namely the poor, middle and upper class. The data is then analyzed by confirmatory method, while the data analysis technique used is Structural Equation Model (SEM) analysis using Amos program version 20. Based on the result of SEM analysis, the result of research shows that the community participation has positive effect on the project success, positive community participation, and community participation together with village head leadership have a positive effect on the success of PNPM Mandiri Rural project in Sukoharjo Village III Sukoharjo Sub-district, Pringsewu District.